Dissection of Antibody Responses of Gam-COVID-Vac-Vaccinated Subjects Suggests Involvement of Epitopes Outside RBD in SARS-CoV-2 Neutralization - Byazrova, Maria; Gattinger, Pia; Astakhova, Ekaterina; Hofer, Gerhard; Khaitov, Musa; Filatov, Alexander; Valenta, Rudolf (International journal of molecular sciences, 2023)
Millions of people have been vaccinated with Gam-COVID-Vac but fine specificities of induced antibodies have not been fully studied. Plasma from 12 naïve and 10 coronavirus disease 2019 (COVID-19) convalescent subjects was obtained before and after two immunizations with Gam-COVID-Vac. Antibody reactivity in the plasma samples (n = 44) was studied on a panel of micro-arrayed recombinant folded and unfolded severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) proteins and 46 peptides spanning the spike protein (S) and by immunoglobulin G (IgG) subclass enzyme-linked immunosorbent assay (ELISA). The ability of Gam-COVID-Vac-induced antibodies to inhibit binding of the receptor-binding domain (RBD) to its receptor angiotensin converting enzyme 2 (ACE2) was investigated in a molecular interaction assay (MIA). The virus-neutralizing capacity of antibodies was studied by the pseudo-typed virus neutralization test (pVNT) for Wuhan-Hu-1 and Omicron. We found that Gam-COVID-Vac vaccination induced significant increases of IgG1 but not of other IgG subclasses against folded S, spike protein subunit 1 (S1), spike protein subunit 2 (S2), and RBD in a comparable manner in naïve and convalescent subjects. Virus neutralization was highly correlated with vaccination-induced antibodies specific for folded RBD and a novel peptide (i.e., peptide 12). Peptide 12 was located close to RBD in the N-terminal part of S1 and may potentially be involved in the transition of the pre- to post-fusion conformation of the spike protein. In summary, Gam-COVID-Vac vaccination induced S-specific IgG1 antibodies in naive and convalescent subjects in a comparable manner. Besides the antibodies specific for RBD, the antibodies induced against a peptide close to the N-terminus of RBD were also associated with virus-neutralization.